NT-proBNP in patients presenting with myocardial infarction and non-obstructive coronary arteries without left ventricular systolic dysfunction - Robert Sykes; Daniel Doherty; Andrew Morrow; Kenneth Mangion; Ahsan Rushd; Colin Berry (American Heart Journal Plus, 2023)
Background: Myocardial infarction and non-obstructive coronary arteries (MINOCA) affects 1 in 9 patients with acute coronary syndrome and has no evidence-based therapy. NT-proBNP is an established biomarker associated with prognosis in heart failure and ischemic heart disease, although there is a paucity of data in patients with MINOCA. Methods: Prospective study of the diagnostic and clinical utility of measuring NT-proBNP in patients with MINOCA without left ventricular dysfunction or heart failure. Data collection was undertaken for patients with an initial diagnosis of MINOCA following urgent coronary angiography in the Golden Jubilee National Hospital (Clydebank, UK), a tertiary center. Demographics were collected in addition to left ventricular function by transthoracic echocardiography. NT-proBNP was measured from a clinically indicated blood sample obtained during routine venepuncture or within the catheter laboratory. Patient outcomes were collected prospectively by the clinical care team using digital follow-up. Results: Fifty-five patients with an initial diagnosis of MINOCA and left ventricular ejection fraction >40 % were included. NT-proBNP was available in 87 % of patients with a median value of 312 pg/mL (interquartile range: 107, 725). Post-discharge, 40 % (n = 24) of patients were readmitted to the hospital, including 15 with chest pain. NT-proBNP ≥125 pg/mL was associated with rehospitalization (P = 0.02). Two patients died and bleeding complications with concomitant antiplatelet therapy occurred in eight patients. Conclusion: NT-proBNP ≥ 125 pg/mL occurred in 72 % of patients presenting with MINOCA and an ejection fraction > 40% and was associated with rehospitalization.